Fatigue and Sleep in Multiple Sclerosis Patients: A Comparison of Self-Report and Performance-Based Measures - Paucke, Madlen; Kern, Simone; Ziemssen, Tjalf (Frontiers in Neurology, 2018)
Background Multiple sclerosis (MS) patients suffer very often from MS fatigue and sleep problems. Despite the detrimental impact on activities of daily living a short and objective quantification of fatigue and sleep problems is currently lacking. Objective The objective of the study was to systematically investigate tonic, intrinsic and phasic alertness and the relationship of these performance-based measures with self-report measures of fatigue and quality of sleep. Methods 33 MS patients without (MS-) and 26 with selected comorbid disorders (MS+) and 43 healthy controls (HC) performed the pupillographic sleepiness test (PST; measuring tonic alertness) and the alertness subtest of the Test of Attentional Performance (TAP; measuring intrinsic and phasic alertness). Results Self-reported and performance based measures revealed poorer performance for both MS groups compared to HC. MS+ patients presented higher rates of MS fatigue, sleep problems and depressive symptoms but similar alertness scores compared to MS- patients. However, tonic alertness was only higher in MS- patients compared to HC. Intrinsic and phasic alertness correlated moderately with fatigue ratings. Conclusion In the diagnostic process of MS fatigue and quality of sleep comorbid disorders (depression, anemia, thyroid dysfunction) and performance-based measures such as alertness should be considered more often in daily clinical practice.